A next-generation IoT-based collaborative framework for electronics assembly - Krishnamurthy, Rajesh; Cecil, J. (International journal of advanced manufacturing technology, 2018)
In today’s dynamic manufacturing environments, the adoption of virtual reality (VR)-based simulation technologies to help in product and process design activities is becoming more widespread. With the onset of the next IT-oriented revolution involving global cyber manufacturing practices, the recent emergence of Internet of things (IoT)-related technologies holds significant promise in ushering an era of seamless information exchange which will provide a robust foundation for the next generation of smart manufacturing frameworks dependent on cyber physical system (CPS)-based principles, approaches, and technologies. In this paper, we present a broad framework for IoT-based collaborations involving the adoption of VR-based analysis environments networked with other cyber physical components. The process context for this VR-centered approach is electronics assembly, which involves the assembly of printed circuit boards. In such manufacturing contexts, it is essential to have a seamless flow of data/information among the various cyber physical components to ensure an agile collaborative strategy which can accommodate changing customer needs. VR-based simulation environments play a key role in this framework which supports multiple users collaborating using haptic interfaces and next-generation network technologies. The simulation outcomes and production data from physical shop floors can be compared and analyzed using this IoT framework and approach.